Definability in partial logic the propositional part - Thijsse, Elias (1990)
Abstract: "This paper addresses to definability (or, more precisely, relative functional completeness) in partial logic with respect to conditions on the set of truth functions. Well-known condition in this area are monotonicity and classical closure. Some isolated definability results are known, whereas other plausible questions have not been answered yet. The aim of this paper is simply to fill in some of these gaps. To this purpose we first present a general framework and the key notion of a closed class and definability w.r.t. a closed class
Teilw. zugl.: Tilburg, Univ., Diss.
Keywords: Logic; Hochschulschrift